Peran Gembala sebagai Pengajar terhadap Pertumbuhan Iman Jemaat - Subekti, Tri (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2020)
The teaching done by a shepherd is one of the important tools in the application of the Word of God that is heard, and also as a means to reach those who already believe and who have not believed in the Lord Jesus according to the command of Jesus in the Book of Matt. 28: 19-20. Shepherd must pay the price for the growth of his church. Many churches today are experiencing difficulties in achieving growth, for this reason the writer is interested in discussing topics that talk about the task that must be carried out by a pastor in achieving church growth. To solve the above problems, researchers conducted research using the survey method and the location of this research was carried out at GBI Galilee Jati Asih Bekasi. Data collection was carried out using observation/observation sheets. To achieve the growth of all fields in the church when this, teaching is the main reference for this growth can be achieved well. Teaching patterns applied in the church has a major influence on quantity growth, growth quality, and spiritual growth. With Conclusion end from the title of the role of the Shepherd As in the Growth of the Galilean GBI Congregation in Jatiasih. One of the main tasks for the pastor in reaching the church's growth is teaching. Because through teaching The Word of God, all members of the congregation will continue to be processed through renewal done by the Holy Spirit.